2017
DOI: 10.1103/physrevc.96.014323
|View full text |Cite
|
Sign up to set email alerts
|

Cross-shell excitations inSi31

Abstract: The 31 nuclei and that previously adapted for 32,34 P. This variation suggests the need for a more universal cross-shell interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This further reduced the deviation from experiment for all sd-shell natural parity states and gave a somewhat more realistic description of the f p shell interaction. In previous publications, we found that corrections to the single particle energies where necessary in order to correctly describe spectra [9,20,21].…”
Section: Spacementioning
confidence: 99%
See 1 more Smart Citation
“…This further reduced the deviation from experiment for all sd-shell natural parity states and gave a somewhat more realistic description of the f p shell interaction. In previous publications, we found that corrections to the single particle energies where necessary in order to correctly describe spectra [9,20,21].…”
Section: Spacementioning
confidence: 99%
“…Comparison with microscopic structure models has proved very fruitful in the past in interpreting level schemes, but were limited by the need to adjust the N = 20 shell gap for cross-shell excitations for different nuclei [9,10,[19][20][21]. Therefore, we decided to develop a microscopic effective interaction based on fitting the shell model cross-shell interaction matrix elements over a wide range of particle-hole states in nuclei across the sd shell and beyond.…”
Section: Introductionmentioning
confidence: 99%